FABRICATION DEVELOPMENT AND PERMEATION STUDIES OF ANTIHYPERTENSIVE DRUG NEBIVOLOL HYDROCHLORIDE TRANSDERMAL PATCHES - Imran, Syed; ., Snehalatha; Nagaraja, T.S.; Bharathi, DR. (Journal of Biomedical and Pharmaceutical Research, 2019)
Nebivolol Hydrochloride is selective Beta blocker having a unique character which distinguishes it from other beta blockers. It increases the release of nitric oxide which causes vasodilation which in turn improves the arterial compliance and decreases the peripheral vascular resistance. The objective of present investigation is to design, evaluate the physical parameters and to carry out the permeation studies of Nebivolol Hydrochloride antihypertensive Transdermal patch by employing suitable polymers such as Eudragit RL100, and Eudragit RS100. The drug and polymer compatibility study has been studied by FTIR and DSC studies. The prepared Nebivolol transdermal patches were subjected various evaluation parameters like weight variation, drug content, moisture content, moisture uptake, thickness uniformity, invitro diffusion study, after performing all evaluation tests, it is confirmed that formulation F2 is the optimized formulation and it shows better invitro diffusion compared to other formulations. Key words: Nebivolol Hydrochloride; TDDS; Eudragit RS100; Eudragit RL 100; Zero order model; Higuchi model; Korsmeyer’s model